Noncompliance, renegotiation, and justice in international adjudication: A WTO-EU perspective - Sivan Shlomo-Agon (Wissenschaftszentrum Berlin für Sozialforschung (WZB), 2015)
Focusing on the expanding realm of international adjudication, this paper approaches justice from the domain of the empirical and shows - through a careful, interview-based case-study analysis in the WTO-EU context - that justice in the transnational context is not only a contested concept, but also a multi-faceted one, deeply embedded in notions such as the rule of law, fairness, equality, transformation, and cooperation. Whereas in the past, the primary, if not the sole role of international courts was that of settling disputes, in their modern legalized reincarnation these empowered international institutions have come to be seen primarily as enforcement mechanisms; mechanisms that have been put in place by states in order to give effect to their originally negotiated commitments and to hold states (or other entities) accountable for the international rules agreed-upon. Within this common enforcement-centered discourse of international courts, in turn, the natural tendency has so far been to think of 'justice' mainly through its 'legal' or 'rule of law' dimension. This paper challenges this enforcement-centered discourse. Focusing on the vibrant WTO dispute settlement system (DSS) and the rich experience of the EU in that system, the paper argues that the current enforcement-oriented debate of international courts, and the WTO DSS in particular, is lacking in several fundamental aspects. First, it brushes aside other important roles served by the DSS, and consequently overshadows the manifold social outcomes - beyond rule-compliance - produced by this system. Second, the prevalent rule-enforcement discourse further works, in turn, as to mask the multiple challenges of justice encapsulated in international disputes reaching the DSS's docket, and obstructs the need to explore other conceptions of justice - beyond its formal legalprocedural meaning - such as global distributive, corrective, or transformative justice, through which the outcomes generated by this international adjudicatory system may (and should) be evaluated. Against this backdrop, the paper puts forwards a broad multifunctional account of the WTO DSS, which goes beyond the prevalent view of the system as primarily an enforcement mechanism, portraying it instead as a system of multiple, competing, and shifting roles. Among them, and at the center of the paper, the role of providing an orderly mechanism of renegotiation, redistribution, and settlement, that essentially allows WTO Members to readjust their original WTO commitments and reallocate their burdens and benefits of international cooperation, and thereby to arrive at new - at times not fully legally-compliant - but not necessarily 'unjust' cooperative and sustainable social outcomes. This discussion paper is part of a series of contributions to the conference "Towards a Grammar of Justice in EU Law', which took place on 6-7 November 2014 at VU University Amsterdam, sponsored by ACCESS EUROPE Amsterdam, VU Centre for European Legal Studies and the Dutch Research Council VENI grant.
Keywords: 320; WTO-EU; international courts; WTO DSS; WTO Members; global judicial system